Emotional Support, Depressive Symptoms, and Age-Related Alterations in Male Body Composition: Cross-Sectional Findings from the Men's Health 40+ Study - Walther, Andreas; Philipp, Michel; Lozza, Niclà; Ehlert, Ulrike (Frontiers in Psychology, 2017)
More depressive symptoms and low emotional support have been related to worse body composition. Body composition significantly deteriorates in aging men. Therefore, we aimed to examine whether high emotional support and low depressive symptoms are associated with better body composition and a decelerated age-related deterioration of body composition in aging men. A cross-sectional analysis including 269 self-reporting healthy men aged between 40 and 75 years living in the German-speaking part of Switzerland was conducted. Participants completed questionnaires on emotional support and depressive symptoms. The depression screening instrument was used to form a group with low (N=225) and moderate (N=44) depressive symptoms. Body mass index (BMI) and waist-to-hip ratio (WHR) were measured, and cell proportion (CP), fat mass (FM), and water balance (WB) were obtained using bioelectrical impedance analysis. Age-related associations emerged for WHR, CP, FM, and WB, but not for BMI. Emotional support was negatively associated with BMI, WHR, and WB, and only trend-wise with CP and FM. Group comparisons revealed that more depressive symptoms were associated with lower levels of CP and higher levels of WB. Both emotional support and depressive symptoms were significant moderators of the association between age and specific measures of body composition such as CP, FM, and WB. However, after correction for multiple testing only the moderation effects of depressive symptoms on the association between age and WB and CP remained significant. Low depressive symptoms were associated with a better body composition as well as a decelerated decline in body composition and the role of emotional support acting as a buffer against age-related deterioration of body composition merits further investigation.